Receptor Tyrosine Kinase Inhibitory Activities and Molecular Docking Studies of Some Pyrrolo[2, 3-d]pyrimidine Derivatives: Receptor tyrosine kinase inhibitory effects of some pyrrolopyrimidine derivatives - Kilic-Kurt, ZÃ¼hal; Emre Kurt, Emin; Bakar-Ates, Filiz (Iranian Journal of Pharmaceutical Sciences, 2019)
In this study, we aimed to determine VEGFR-2, EGFR and PDGFR-β tyrosine kinase inhibitory activities of some pyrrolo[2,3-d]pyrimidine derivatives previously synthesized and showed potent cytotoxic and apoptotic effects against several cancer cell lines by our group and to evaluate the relationships between inhibitory activities and binding properties of the active compounds by molecular docking studies. VEGFR-2, EGFR ve PDGFR-β tyrosine kinases inhibitory activities of the tested compounds were determined using KDR Kinase Enzyme System Analysis Kit (Promega, #V2681), EGFR Kinase Enzyme System Analysis Kit (Promega,#V3831) and PDGFR-β Kinase Enzyme System Analysis Kits (Promega, #V3731) according to the manufacturer’s instructions. The molecular docking studies were performed using Autodock vina program.Compounds 9a, 9b and 11b exhibited the weak inhibitory activities against VEGFR-2, EGFR and PDGFR-β,respectively. Molecular docking studies showed that one or two hydrogen bonding interactions were found between compounds 9a, 9b, 11b and VEGFR-2, EGFR, PDGFR-β tyrosine kinases. Biological activity and molecular docking results revealed that interactions of compounds with target protein active sites are not enough to obtain potent RTK inhibitory activity. It is necessary to design some compounds showing more interactions with the target proteins to obtain better activity results.